Vezetői kompetenciák felmérése a szállodaipar különböző szegmenseiben - Somlai Réka (Taylor : gazdálkodás- és szervezéstudományi folyóirat, 2017)
The leadership roles and competences in the tourism industry are different than at any other fields. The characteristics of the field specify what are the competences and skills what leaders especially need to have to be successful. In tourism life never stops, work must run 24 hours a day, guests must be satisfied, there are cultural, ethnical and religion differences, average salary are lower than at other fields. According to international researches in tourism inter- and intrapersonal skills are more important than other managerial soft skills. There has not be made any similar Hungarian researches yet about what are the skills and competences what managers need to have in hospitality, therefore a research examining Hungarian sample is necessary. Present research was inspired to study what are the main skills and competences what hospitality managers use on the daily basis and analyses specific skills (assertiveness, emotional intelligence, conflict resolution, leadership skills). The research examined different segments of tourism starting from hostels to five star hotels. Results can be useful for further studies in hospitality.